Tradition and Innovation in the Education of the Mongolian State University of Education: Art and Cultural Education in Mongolia (Journal of Interdisciplinary Insights, 2024)
Mongolia has outlined its long-term development vision through the "Vision-2050" strategy, and the medium-term development plan for the education sector (2021-2030), alongside government action programs. These strategies emphasize the goal of ensuring equitable access to quality education for all citizens, and strengthening the system of inclusive education. As we move forward in the era of social and digital technologies, the planning of future educational developments and reforms, including in the fields of arts, music education, and the development of citizens with social activism, continuous learning capabilities, and ethical integrity, becomes essential. The development of modern music education in Mongolia and the role of the Mongolian State University of Education's Faculty of Education in shaping music teacher training, as well as addressing issues such as the lack of outstanding talents emerging from the current educational system, are critical concerns. This study aims to analyze the shortcomings of music education and propose solutions for addressing these gaps.
Keywords: Music; Education; Teacher; Training; Development